The relationship between sitting duration and piriformis syndrome in handcrafters - Ida Ayu Harnum Febry Wiguna; Anak Ayu Nyoman Trisna Narta Dewi; I Made Niko Winaya (Universitas Udayana dan Diaspora Taipei Medical University, 2024)
Background: Handcrafters of serati banten are professionals at risk of developing piriformis syndrome. This can happen because serati banten's working position is sitting for a long time. If this position is carried out continuously for a long period, it can cause musculoskeletal symptoms, namely piriformis syndrome. This study aimed to determine the relationship between sitting duration and piriformis syndrome in handcrafters of serati banten. Methods: This research was an analytical observational study with a cross-sectional study design conducted from June to December 2023. Sampling was done using a purposive sampling technique with a total sample of 106 people in this study. This study's inclusion criteria were handcrafters of serati banten aged 45 to 55. The exclusion criteria included experiencing low back pain. The independent variable measured was sitting duration, determined by filling in the questionnaire, and the dependent variable measured was piriformis syndrome, calculated using the flexion adduction internal rotation test, active piriformis test, and pace test. Results: Based on the chi-square test results, the value of p=0.003 (p<0.05) was obtained, meaning a significant relationship exists. Conclusion: There was a significant relationship between sitting duration and piriformis syndrome in handcrafters of serati banten.